Thermal elastohydrodynamic lubrication characteristics and optimisation of the ball-type tripod universal joint. Issue 10 (12th November 2021) - Yang, Fuqin; Han, Xiaojie; Si, Mingqing
Abstract : Purpose: This paper aims to study the influence of three-column groove shell radius, ball radius, lubricating oil viscosity and elastic modulus on the thermal elastohydrodynamic lubrication (TEHL) characteristics and optimisation of the ball-type tripod universal joint. Design/methodology/approach: The point contact TEHL model of the joint was developed, and the multi-grid method was used to solve it. The influence of three-column groove shell radius, ball radius, lubricating oil viscosity and elastic modulus on the lubrication characteristics was analysed. Further, the optimisation of the joint TEHL performance was carried out by the Kriging approximation model combined with the multi-objective particle swarm optimisation (MOPSO) algorithm. Findings: The research results show that increasing groove shell radius and ball radius can effectively increase the oil film thickness, and decrease the oil film pressure, as well as the temperature rise. Decreasing elastic modulus can reduce the oil film temperature rise and pressure, and increasing viscosity can effectively increase the oil film thickness. The optimised minimum oil film thickness increases by 33.23% and the optimised maximum oil film pressure and maximum temperature rise decrease by 11.92% and 28.87%, respectively. Furthermore, the relative error of each response output is less than 10%. Originality/value: This study applies TEHL theory to the tribological research of the ball-type tripod universal joint, and the joint's lubrication performance is improved greatly by the Kriging model and MOPSO algorithm, which provides an effective measure to raise the joint's working efficiency.